New nomenclatural combinations in Nitrosalsola (Chenopodiaceae) - Feodorova, T.A. (Український ботанічний журнал, 2015)
Thirty-two new nomenclatural combinations are validated in the genus Nitrosalsola Tzvelev
(Chenopodiaceae). The genus, as newly outlined, contains both annual and perennial (shrubs and
subshrubs) species earlier treated in some infrageneric groups of Salsola L. s. l., or recently transferred to
Caroxylon Thunb. The new circumscription of Nitrosalsola, its morphological characters, and the need
for its segregation from Caroxylon are briefly discussed Тридцять дві нові номенклатурні комбінації запропоновано в роді Nitrosalsola Tzvelev (Chenopodiaceae). Цей рід у
новому розумінні містить як однорічні, так і багаторічні
види (напівкущі та напівкущики), які раніше розглядали
в межах деяких внутрішньородових груп роду Salsola L.
s.l. або які нещодавно були перенесені до роду Caroxylon
Thunb. Стисло обговорені новий обсяг роду Nitrosalsola,
його морфологічні ознаки та необхідність виділення зі
складу Caroxylon і Salsola. Тридцать две новые номенклатурные комбинации предложены в роде Nitrosalsola Tzvelev (Chenopodiaceae). Этот
род в новом понимании содержит как однолетние, так
и многолетние виды (полукустарники и полукустарнички), которые ранее рассматривались в составе некоторых внутриродовых групп рода Salsola L. s.l. или недавно
были перенесены в род Caroxylon Thunb. Кратко обсуждены новый объем рода Nitrosalsola, его морфологические признаки и необходимость его выделения из состава родов Caroxylon и Salsola.